Analysis of the Level of Public Satisfaction with the Government's Policy to Revoke the Rules for the Use of Masks in Public Places - Sukmana, Hendra; Choiriyah, Ilmi Usrotin; Agustina, Isna Fitria (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2022)
The purpose of this study is to analyze the level of public satisfaction with the government's policy of revoking the rules for using masks in public places. Data analysis was carried out by descriptive quantitative analysis. The results of the analysis obtained an average of 77.7 and when referring to the category of community satisfaction, the value is included in the satisfied category. In this regard, the general public is satisfied with the government's policy of revoking the rules for using masks in public places. On the day of May 2022 President Joko Widodo (Jokowi) decided to relax the policy on the use of masks outdoors. One of the most important things to reach this stage is the understanding of the community regarding healthy living behavior which is the responsibility of each individual. Easing was also carried out taking into account the development of the Covid-19 situation in the world. If you look at the development of Covid-19 in Indonesia and globally, the Indonesian people already have resistance to new variants. Several people admitted that they were happy with the policy of loosening the use of masks in open spaces because they were considered easier to breathe, carry out activities and not feel stuffy.